On the microstructure evolution and fracture behavior of titanium alloy plates subjected to underwater explosion - Pan Zhang; Yuan Guo; Jianhui Wei; Fei Yan; Chang Ye; Xiaoyang Lu; Peng Jiang; Yuansheng Cheng (Journal of Materials Research and Technology)
Titanium alloy has attracted interest for potential applications to exploit its high specific strength and excellent impact energy absorption. The objectives of current study are to examine the dynamic behaviors of the Ti80 alloy plates with different heat treatment processes in response to underwater explosion. Several shock tests were conducted to analyze the microstructure evolution and fracture behaviors. Metallographic examinations indicate that α phase in specimens with normal annealing would transform from globular morphology to ''worm-like'' or banded morphology. βtrans structures with lamellar αs phase and lamellar β phase in solution-treated specimens were constantly compressed due to their low hardness. Among the heat-treated specimens, the β annealed specimen owns the most large-angle grain boundaries, resulting in high texture intensity and anisotropy of materials. The formation of α phase at the grain boundary and coarse original β grain boundaries deteriorated the performance of the β annealed specimen against underwater explosion. In contrast, the solution heat-treatment process could improve the elongation property and further benefit large plastic deformation to avoid the premature cracking failure. Finally, a preliminary model was proposed to elaborate the toughening mechanism of Ti80 alloy plates subjected to underwater explosion.